Linguistic prejudice: Situations experienced within the school context - Araujo, Marcilene de Assis Alves; Araújo, Ilka da Graça Baía de; Costa, Domingas Ferreira; Fontenele, Eslaine Ferreira Teixeira (Seven Editora, 2023)
This study aimed to investigate how linguistic prejudice manifests in the learning process of 6th, 8th, and 9th grade students in a public school in the municipality of Gurupi, TO, Brazil. The interest in this subject matter arose from the studies and discussions in Linguistics classes during the undergraduate program in Bachelor’s Degree in Languages - Portuguese/English, supported by the internship experience, where it was observed that Portuguese language instruction in schools had a traditionalist approach, centered on normative grammar as the only acceptable language variation, disregarding other linguistic varieties. Consequently, this led to language  prejudice against other varieties that were strongly ignored in the formal school setting. Based on these observations, the following research question guided the study: What learning situations can be implemented to mitigate linguistic prejudice experienced by students from the 6th grade onwards in elementary school? To answer this question, a research methodology combining literature review with a field study of qualitative approach was employed, involving observation, informal conversations, focus groups, and activities aimed at innovative practices related to the subject matter. The research results were promising, providing significant contributions to the main objective of the study. They demonstrated that working with active methodologies and strategies based on discourse genres and multiliteracies positively influences the reduction of linguistic prejudice in relation to the use of formal language. This, in turn, fosters students’ development and learning. DOI:https://doi.org/10.56238/alookdevelopv1-120